Convent wisdom : how sixteenth-century nuns could save your twenty-first-century life - Garriga, Ana; Urbita, Carmen (Avid Reader Press, 2025)
"When most of us think of nuns, we picture hands clasped in prayer, solemn shuffles down cloistered halls, and that iconic habit silhouette. But what about the nuns who ate spiderwebs, erupted into jealous fights over makeup, or chain-produced manuscripts for extra cash? In reality, these women were no one-dimensional martyrs. 16th- and 17th-century nuns were resourceful, rebellious, and refreshingly relatable--and their lives hold surprising lessons for us today. Convent Wisdom is your guide to navigating everything from patriarchal bureaucracy to an all-consuming friend crush with help from history's most fascinating nuns. Struggling with money? Saint Teresa and her fellow Carmelites have recession-proof advice. Scrolling social media and drowning in FOMO? Mary of Jesus of Ágreda's miraculous ability to engage in bilocation might help you cope. Confounded by a lesbian situationship? The yearnings of Sor Juana Inés de la Cruz contain unexpected insights. Blending rigorous research with tongue-in-cheek takeaways and weaving pop culture and personal anecdotes throughout, Brown University scholars and best friends Ana Garriga and Carmen Urbita spill the juicy inside scoop on monastic life so you can better conquer today's anxiety-ridden, hyper-connected world. Be it work woes, unholy diets, or crises of the soul, the nuns of Convent Wisdom are here to guide you--with a wink and a prayer." --